2018
DOI: 10.3390/toxins10030117
|View full text |Cite
|
Sign up to set email alerts
|

G Protein α Subunit GpaB is Required for Asexual Development, Aflatoxin Biosynthesis and Pathogenicity by Regulating cAMP Signaling in Aspergillus flavus

Abstract: The heterotrimeric G proteins are critical for signal transduction and function in numerous biological processes including vegetative growth, asexual development and fungal virulence in fungi. Here, we identified four G protein alpha subunits (GanA, GpaB, FadA and GaoC) in the notorious Aflatoxin-producing fungus Aspergillus flavus. GanA, GpaB and FadA have homologues in other fungal species, while GaoC is a novel one. Here, we showed that the loss function of gpaB displayed a defect in conidiophore formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
1
21
0
2
Order By: Relevance
“…Unlike our results, the phenotype of the ∆gpaB mutant in A. flavus is slightly different. The colony size of the ∆gpaB mutant was increased compared to that of WT and complemented strains [12], suggesting that the roles of GpaB may not be conserved in Aspergillus.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Unlike our results, the phenotype of the ∆gpaB mutant in A. flavus is slightly different. The colony size of the ∆gpaB mutant was increased compared to that of WT and complemented strains [12], suggesting that the roles of GpaB may not be conserved in Aspergillus.…”
Section: Discussionmentioning
confidence: 96%
“…In A. nidulans, the G protein mediates cAMP signaling are required for sterigmatocystin biosynthesis [11]. In A. flavus, The Gα subunit GpaB is also essential for the biosynthesis of aflatoxins, and aflatoxin production was drastically inhibited by the loss gpaB [12]. Despite the small difference in the amounts, the Gα encoding gene deletion mutants of A. fumigatus produced less GT than the WT strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In eukaryotes, it has been reported that cAMP activates the protein kinase A (PKA) pathway by binding to the regulatory subunit (PkaR) that leads to its dissociation from the catalytic subunit (PkaC), which activates several transcription factors that control the final morphological fate of the cell (Choi, Jung, & Kronstad, 2015). The fungal PKA pathway is involved in several functions, including asexual sporulation, nutrient sensing, growth and virulence (Demuyser, Van Genechten, Mizuno, Colombo, & Van Dijck, 2018;Fuller & Rhodes, 2012;Kozubowski, Lee, & Heitman, 2009;Liu et al, 2018).…”
Section: The Addition Of Camp To Cultures Of Diverse Dimorphic Speciementioning
confidence: 99%
“…The biosynthesis of these SMs cannot only be controlled by the intra-cluster regulating genes but can also be adjusted by the off-cluster global regulating genes, such as Lae A, Ve A, and related genes in the G-protein signaling pathway (GPSP) (Fox and Howlett, 2008; Liu Q. et al, 2016; Lin et al, 2018). GPSPs, including the G-protein coupled receptor (GPCR), heterotrimeric G-protein (G-protein) and downstream effectors (Seo and Yu, 2006), play vital roles in growth, differentiation, SMs biosynthesis, pathogenicity and toxicity in filamentous fungi (Yu et al, 2008; Corrochano et al, 2016; Moretti et al, 2017; Liu et al, 2018; van den Hoogen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%